Albendazole therapy for eosinophilic meningitis caused by Angiostrongylus cantonensis - Jitpimolmard S. (2014)
Eosinophilic meningitis in humans is commonly caused by the nematode Angiostrongylus cantonensis. A severe headache is the most common presenting symptom. A prospective, randomized, double-blind, placebo, controlled study was conducted to determine if albendazole was efficacious in relieving such headaches. Seventy-one patients (36 and 35 in the treatment and control groups) were enrolled in the study. Five patients (two and three in the treatment and control groups) were excluded from the study because of being lost to follow-up, and the clinical data were incomplete. Therefore, 34 and 32 patients in the treatment and control groups were studied, respectively. Albendazole was administered at 15 mg/kg/day or identical placebo for 2 weeks. The number of patients with persistent headaches after 2 weeks was 7 and 13 in the albendazole and placebo groups (p=0.08), respectively. The mean duration of a headache was 8.9 and 16.2 days in the albendazole and placebo groups, respectively (p=0.05). No serious drug events were observed. A 2-week course of albendazole appeared to reduce the duration of headache in eosinophilic meningitis. © 2006 Springer-Verlag.